Kebijakan Penanganan Terorisme di Kabupaten Poso - Roma Tressa (Jurnal Ilmiah Administratie, 2021)
The horizontal conflict which was considered resolved through the Malino peace agreement in 2001 continued with the emergence of terrorism crimes in Poso Regency. The objective of this article is to describe the policy on dealing with terrorism in Poso Regency from 2012 to 2021. The finding obtain that the handling of terrorism is dominated by the role of TNI and Polri through security operations which refers to Perkap No. 9 of 2011 concerning Police Operations Management. Police operations to counter terrorism are formally decided in an operation plan, where each operation uses a certain code, namely Operasi Kendali Maleo I to V 2012, Operasi Aman Maleo I to IV 2013, Operasi Aman Maleo I to !V 2014, Operasi Camar Maleo I to IV 2015, Operasi Tinombala I to IV 2016, Operasi Tinombala I to III 2017 and Operasi Tinombala 2018 to 2019, and Operasi Madago Raya 2020-2021